2020
DOI: 10.1515/npprj-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Plantago psyllium seed husk flour on the properties of cellulose sheet

Abstract: This study examined the use of Plantago psyllium seed husk flour as paper additive with the aim of improving the properties of cellulose sheet. The husk flour was added in 5 wt%, 10 wt%, 20 wt% and 30 wt% to the cellulose suspensions and its effect on the handsheet properties was studied. The results showed that the direct addition of husk flour highly improves the mechanical properties of the handsheets like tensile index (with up to 400 %), burst index (with up to 600 %) and tear index (with up to 1200 %). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Köhnke et al (2011) also found that amount of xylan absorbed which is time dependent has an effect on the tensile index, which first shows an increase and then reached a maximum value. Halász et al (2020) in a previous research was investigated that the sheets made from primary fiber modified with Plantago psyllium seed husk flour, had a significant improvement its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Köhnke et al (2011) also found that amount of xylan absorbed which is time dependent has an effect on the tensile index, which first shows an increase and then reached a maximum value. Halász et al (2020) in a previous research was investigated that the sheets made from primary fiber modified with Plantago psyllium seed husk flour, had a significant improvement its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Köhnke et al (2011) also found that amount of xylan absorbed which is time dependent has an effect on the tensile index, which first shows an increase and then reached a maximum value. Halász et al (2020) in a previous research was investigated that the sheets made from primary fiber modified with Plantago psyllium seed husk flour, had a significant improvement its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%